Analisis Kemampuan Menyimak dalam Mengidentifikasi Unsur-Unsur Berita pada Siswa Kelas VIII SMP Negeri 1 Singingi - Sandria, Wilvi; Tinambunan, Jamilin (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
This study tries to describe, analyze, and interpret the abilities of class VIII students of SMP Negeri 1 Singingi, Singingi District, Kuantan Singingi Regency for the 2022/2023 academic year in determining the elements of the news to be listened to. This study aims to answer the question of how well students are capable in this regard. The population in the study were 23 students of class VIII.1, and the sample used was a saturated/total sample. The research method used is descriptive with a quantitative approach and uses the theory of several experts. The results showed that the students' ability to determine news elements was in a good category with a score of 78.98. Thus, the previously established hypothesis that the students' ability to determine news elements is only sufficient with a range of 56-65 scores must be rejected because the category of scores achieved by students is in the good category.